EVALUATION OF ANTIMICROBIAL POTENTIALS OF Cardiospermum halicacabum Linn. - Veerappan, Loganathan; T, Thirunala Sundari; N, Pradheepa (Indonesian Journal of Pharmacy, 2013)
Antimicrobial activity of Cardiospermum halicacabum shoot extracts were studied on gram-positive bacteria such as Staphylococcus aureus, Bacillus substilis, and gram-negative bacteria such as E.coli, Proteus vulgaris, and fungus Candida albicans. Disc diffusion method was used to study the antimicrobial activity of aqueous, ethanol, chloroform and ether extracts of C. halicacabum. Ampicillin was used as reference standard at 10 mg/disc concentration. Extracts of C. halicacabum exhibited a significant antibacterial activity except the aqueous extract. Ethanolic extract was found to be very effective with maximum activity index (0.84). The ethanolic extract exhibited minimum inhibitory concentration (MIC of 0.25 mg/mL against Staphylococcus aureus, Bacillus substilis, E. coli and Proteus vulgaris and 0.125 mg/mL against Candida albicans. The MIC of chloroform and ether extracts ranged between 0.25 and 1.0 mg/ml against the test organisms. All the extracts showed antifungal activity against Candida albicans. Key words: antimicrobial activity, Cardiospermum halicacabum shoot system, solvent extraction,.